1995
DOI: 10.1073/pnas.92.26.12070
|View full text |Cite
|
Sign up to set email alerts
|

T-cell-specific deletion of a polypeptide N-acetylgalactosaminyl-transferase gene by site-directed recombination.

Abstract: UDP-N-acetylgalactosamine (GalNAc): polypeptide N-acetylgalactosaminyltransferase (polypeptide GalNAc-T) catalyzes transfer of the monosaccharide GalNAc to serine and threonine residues, thereby initiating 0-linked oligosaccharide biosynthesis. Previous studies have suggested the possibility of multiple polypeptide GalNAc-Ts, although attachment of saccharide units to polypeptide or lipid in generating oligosaccharide structures in vertebrates has been dependent upon the activity of single gene products. To ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
186
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(192 citation statements)
references
References 28 publications
5
186
0
1
Order By: Relevance
“…The Tak1 flox/flox mice were born and lived normally, and they expressed TAK1 protein as expected (data not shown). To delete the Tak1 allele specifically in T cells, we crossed Tak1 flox/flox mice with the Lck-Cre transgenic mice, which express the Cre recombinase under the control of the T cell-specific Lck promoter (21). Southern blotting and PCR showed that the floxed Tak1 alleles were excised in thymocytes, but not in the tail (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tak1 flox/flox mice were born and lived normally, and they expressed TAK1 protein as expected (data not shown). To delete the Tak1 allele specifically in T cells, we crossed Tak1 flox/flox mice with the Lck-Cre transgenic mice, which express the Cre recombinase under the control of the T cell-specific Lck promoter (21). Southern blotting and PCR showed that the floxed Tak1 alleles were excised in thymocytes, but not in the tail (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Blastocyst injection was performed at Baylor College of Medicine. Lck-Cre transgenic mice were obtained from The Jackson Laboratory (21). Floxed Tak1 mice were crossed to Lck-Cre mice at University of Texas Southwestern Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…1). Lck-Cre transgenic mice express the Cre recombinase under the control of the Lck proximal promoter, which drives the Cre expression specifically in immature thymocytes (27,29).…”
Section: Methodsmentioning
confidence: 99%
“…This resulted previously in the establishment of mice lacking an intact gene for pp-GalNAc-T13 by using the pp-GalNAc-T1 gene as a probe for cloning, and prior to evidence for multiple pp-GalNAc-T isozymes (26,27). In the previous study (27), the complete gene encoding pp-GalNAc-T13, which was partially identified and tentatively designated mouse pp-GalNAc-T8, was never cloned and characterized.…”
Section: The Nucleotide Sequence(s) Reported In This Paper Has Been Smentioning
confidence: 99%